Structural studies of the water pentamer (2011)
ABSTRACT: A computational study of the water pentamer gas phase conformational space is reported in this Letter. Forty-four stationary points distributed among 12 structural patterns were located at the MP2/6– 311++G(d,p) level. At least 5 geometrical motifs (25 structures) are predicted within 3 kcal/mol of the most stable conformation at the CCSD(T)/aug–cc–pVTZ//MP2/6–311++G(d,p) level. We show evidence that dipole–dipole interactions are at play in stabilizing the clusters. Electron densities and their Laplacians at the hydrogen bond critical points were found to be linearly correlated with relative energies for all clusters. Logarithmic relationships were found for the ½req; qðrc Þ and ½req; r2 qðrc Þ pairs in all hydrogen bonds.